BIMBINGAN QUR’AN DENGAN METODE AS’SYAFI’I DI TK/TPA MESJID DARUL AFTAR DUSUN KATUTE DESA BARAMBANG - Sulaiman, Sulaiman (LP2M Universitas Islam Ahmad Dahlan, 2024)
The Qur'an is the word of God that was sent to the Prophet Muhammad through the intermediary of the angel Gabriel, who is the guide of human life, especially those who are Muslim. In maintaining the Qur'an, it is necessary to learn things related to the Qur'an, both how to read and apply the science of tajwid. Children in Barambang village need the name of tajwid knowledge development because of the lack of educators who focus on quran education, so that children can understand the concept of reading the Koran properly and correctly in accordance with the provisions.